An Investigation into Loss and Gain in the Vietnamese Translation Autobiography “My Life” by Bill Clinton - Nguyen Phuong Thao
Chapter 1. Introduction; Chapter 2. Literature review and theoretical background; Chapter 3. Research design and methodology; ...